7.26 MEASURES TO PREVENT LOOTING IN THE AREA OF PUBLIC UTILITIES - Normakhamedov Baburbek Khusanboy ugli Graduate Master of Law Enforcement Academy of the Republic of Uzbekistan (Innovative technologies in construction Scientific Journal, 2024)
This article discusses the Basic Rules and procedure for the investigative action of interrogating looting in the field of Public Utilities, the procedure for formalizing the results of this investigative action and its importance in the investigation of criminal cases. The main methods of obtaining evidence through interrogation by interrogators and investigators are analyzed. KEYWORDS: investigative action, interrogation, investigator, interrogator, suspect, accused, legality, admissibility of evidence. АҲОЛИГА КОММУНАЛ ХИЗМАТ КЎРСАТИШ СОҲАСИДАГИ ТАЛОН-ТАРОЖЛАРНИ ОЛДИНИ ОЛИШ ЧОРА ТАДБИРЛАРИ АННОТАЦИЯ. Мазкур мақолада аҳолига коммунал хизмат кўрсатиш соҳасидаги талон-тарожларни сўроқ қилиш тергов ҳаракатининг асосий қоидалари ва тартиби, ушбу тергов ҳаракатининг натижаларини расмийлаштириш тартиби ҳамда жиноят ишларини тергов қилишдаги аҳамияти муҳокама қилинади. Суриштирувчи ва терговчилар томонидан сўроқ қилиш орқали далилларга эга бўлишнинг асосий усуллари таҳлил қилинади. КАЛИТ СЎЗЛАР: тергов ҳаракати, сўроқ, терговчи, суриштирувчи, гумон қилинувчи, айбланувчи, қонунийлик, далиллар мақбуллиги. INTRODUCTION. Further deepening the democratic foundations of the judicial system in our country, forming the foundations of national legislation, ensuring the fight against crime at the level of contemporary requirements, improving the effectiveness of the activities of law enforcement agencies were established as one of the priorities of state policy, in this regard, ensuring human rights and freedoms and protection were recognized as an important factor. As a clear confirmation of this, we will be able to see the example of the decree of the president of the Republic of Uzbekistan of August 10, 2020 "on measures to further strengthen the guarantees of the protection of the rights and freedoms of the individual in judicial and investigative activities"[1]. The adoption of this decree was an important step to ensure unconditional observance of the rights and freedoms of the individual, to improve the quality of procedural actions, to collect and consolidate evidence in the criminal process, to introduce new mechanisms taking into account the standards of proof widely used in advanced foreign experience of the Assessment System[2]. And in addition, the population is strengthened by the criminal and administrative work that is taking place in the communal services systems. Reforms in the field of Public Utilities are an integral component of the socio-economic re-transformations carried out in the Republic and are being implemented on the basis of the legislation and normative and legal framework for which it was created. Reform of the system of Housing and communal services for the population "on the privatization of the state housing fund"," on the basis of the state housing policy "of the president of the Republic of Uzbekistan"on improvement of the management of municipal services in the Republic of Uzbekistan", The decrees of the Cabinet of Ministers"on measures to promote and develop housing construction in the Republic" dated February 7, 1994 No. 54 "on measures to improve the provision of utilities to the population in the conditions of market economies" dated April 25, 1997 No. 211 and other legislative and regulatory legal acts are implemented in accordance with the decisions the process of their transition to their relationship began.